Slavery in the Circuit of Sugar, Second Edition Martinique and the World-Economy, 1830-1848 - Tomich, Dale W. (SUNY Press Open Access, 2016)
A classic text long out of print, Slavery in the Circuit of Sugar traces the historical development of slave labor and plantation agriculture in Martinique during the period immediately preceding slave emancipation in 1848. Interpreting these events against the broader background of the world-economy, Dale W. Tomich analyzes the importance of topics such as British hegemony in the nineteenth century, related developments of the French economy, and competition from European beet sugar producers. He shows how slaves' adaptation-and resistance-to changing working conditions transformed the plantation labor regime and the very character of slavery itself. Based on archival sources in France and Martinique, Slavery in the Circuit of Sugar offers a vivid reconstruction of the complex and contradictory interrelations among the world market, the material processes of sugar production, and the social relations of slavery. In this second edition, Tomich includes a new introduction in which he offers an explicit discussion of the methodological and theoretical issues entailed in developing and extending the world-systems perspective and clarifies the importance of the approach for the study of particular histories.